Fabry pedigree analysis: A successful program for targeted genetic approach - Rozenfeld, Paula Adriana (2019)
Background: Fabry disease (FD) is an X-linked disorder of glycosphingolipid catabolism caused by a deficiency of the lysosomal enzyme alpha-galactosidase A (GLA). FD is still an underdiagnosed disorder worldwide. Moreover, there is delay between symptom onset and Fabry diagnosis of at least 10 years. Family screening offers an important benefit for detection of new patients. The aim of this work is to present the approach along with the results of a targeted genetic strategy for pedigree analysis for FD in Argentina. Methods: By this strategy as soon as a new index Fabry patient is diagnosed, the pedigree group contacts the physician and a meeting is arranged with the physician and the family to build the family tree. Results: Pedigree analysis was carried out for full in 31 families. In the work period, we have tested 1,462 relatives, and 501 were diagnosed FD. The proportion of positive detection was 33%. Conclusion: The targeted family screening approach is successful to detect undiagnosed Fabry patients. By this approach, the highest ratio index to pedigree ever reported for FD pedigree analysis of 1:15 was obtained.